2018
DOI: 10.1038/s41598-018-25374-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of immunogenic properties of Hemolin from silkworm, Bombyx mori as carrier protein: an immunoinformatic approach

Abstract: Infectious diseases are the major cause of high mortality among infants and geriatric patients. Vaccines are the only weapon in our arsenal to defend us ourselves against innumerable infectious diseases. Though myriad of vaccines are available, still countless people die due to microbial infections. Subunit vaccine is an effective strategy of vaccine development, combining a highly immunogenic carrier protein with highly antigenic but non–immunogenic antigen (haptens). In this study we have made an attempt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The insect immune response against various external invasions is a complex process, and some immune genes are lepidopteran-specific. Hemolin is a lepidopteran-specific gene that encodes a pattern recognition protein that can be induced by bacteria and viruses (Aathmanathan et al, 2018). HaREase is also lepidopteran-specific gene (Guan et al, 2018b), study these lepidopteran specific genes will help in understanding the specific immune pathway of these insects and contribute to the management of cotton bollworm.…”
Section: Discussionmentioning
confidence: 99%
“…The insect immune response against various external invasions is a complex process, and some immune genes are lepidopteran-specific. Hemolin is a lepidopteran-specific gene that encodes a pattern recognition protein that can be induced by bacteria and viruses (Aathmanathan et al, 2018). HaREase is also lepidopteran-specific gene (Guan et al, 2018b), study these lepidopteran specific genes will help in understanding the specific immune pathway of these insects and contribute to the management of cotton bollworm.…”
Section: Discussionmentioning
confidence: 99%
“…5 g and 6g , virtual complexes of AdipoRon, Tyr-Pro, Pro-Tyr, and Trp-Pro with the AdipoR1 protein anchored in the POPC membrane provided constant protein backbone root-mean-square deviation (RMSD) values of 2.0–5.0 Å for MD simulations at sites 1 and 2, respectively. Considering the results from previous studies that the protein RMSD value in MD simulation was stable at 2.0–9.0 Å 23 , the virtual systems developed in this study between targets and the AdipoR1 receptor were stably simulated during the MD docking analyses (Movies S 1 – 8 ). The virtually complexed forms also revealed that the AdipoR1 agonistic Tyr-Pro dipeptide was stabilized at the inner position of each pocket in AdipoR1 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Hemolin aids haemocyte aggregation and phagocytosis of foreign cells through recognition of lipopolysaccharide (LPS) and lipoteichoic acid (LTA) of Gram-negative and -positive bacteria, as well as fungal β-1,3-glucan ( Eleftherianos et al., 2007 ; Jung et al., 2019 ). Hemolin opsonizes microbial pathogens and binds to haemocytes, enhancing phagocytic uptake and eliminating invading pathogens ( Aathmanathan et al., 2018 ). The interaction of hemolin with the structurally unique mycobacterial cell wall has not been described.…”
Section: Discussionmentioning
confidence: 99%